Penggunaan Kata Kurios Bagi Yesus Sebagai Argumentasi Pembuktian Ketuhanan Yesus - Febrianto, Carles; Monica, Gledys Sandra (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This study aims to analyze the use of the term Kurios for Jesus in the New Testament as a basis for theological argumentation to prove His divinity. The term Kurios, meaning “Lord,” has a significant background in the Septuagint tradition, where it was used to translate the name of God (YHWH) in the Old Testament. This study employed a qualitative, exegetical approach, encompassing contextual, grammatical, lexical, historical, and theological analyses of crucial texts. The results show that the use of the term Kurios is not only honorific but also an explicit recognition of Jesus divinity within the context of the early church's faith. Thus, the term Kurios provides a strong biblical foundation for the doctrine of Jesus' divinity in Christian theology.